Zapisz bez nawiasów:
3p - 2(8q - 4p) =
-7 (a - 3b) + 7 =
-2 (-2a + 5) - (-3a) =
2x - 1/2 (-6x + 4) =
-0,8(5q + 7p) - 4p =

Przekształć wyrażenia w sumę i wykonaj redukcję wyrazów podobnych. :
2(a-6) - 9a =
-7(b + 4) + 11 =
-4y - 7(8-9y) =
7p - (-3p + 6) razy 8 + 12 =

2

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-23T15:58:28+01:00
Zapisz bez nawiasów:
3p - 2(8q - 4p) =3p-16q+4p=7p-16q
-7 (a - 3b) + 7 = -7a+21b+7
-2 (-2a + 5) - (-3a) = 4a-10+3a=7a-10
2x - 1/2 (-6x + 4) =2x+3x-2=5x-2
-0,8(5q + 7p) - 4p = -4q -5,6p -4p =4q-9,6p

Przekształć wyrażenia w sumę i wykonaj redukcję wyrazów podobnych. :
2(a-6) - 9a = 2a-12-9a= -7a-12
-7(b + 4) + 11 = -7b -28+11= -7b-17
-4y - 7(8-9y) = -4y - 56+ 63y = 56+59y
7p - (-3p + 6) razy 8 + 12 = (10p -6) 20= 200p-120

2010-02-23T16:04:39+01:00
3p - 2(8q - 4p) =3p - 16q + 8p
-7 (a - 3b) + 7 =-7a+21b +7
-2 (-2a + 5) - (-3a) = 4a - 10 + 3a
2x - 1/2 (-6x + 4) =2x + 3x - 2
-0,8(5q + 7p) - 4p = -4q - 5,6p - 4p


2(a-6) - 9a = 2a - 12 - 9a = -7a - 12
-7(b + 4) + 11 = -7b -28+11= -7b-17
-4y - 7(8-9y) = -4y - 56 + 63y = -56 + 59y
7p - (-3p + 6) razy 8 + 12 = (10p -6) 20= 200p-120